2020
DOI: 10.1080/2150704x.2020.1767823
|View full text |Cite
|
Sign up to set email alerts
|

Validation of sentinel-2 leaf area index (LAI) product derived from SNAP toolbox and its comparison with global LAI products in an African semi-arid agricultural landscape

Abstract: This study validated SNAP-derived LAI from Sentinel-2 and its consistency with existing global LAI products. The validation and intercomparison experiments were performed on two processing levels, i. e., Top-of-Atmosphere and Bottom-of-Atmosphere reflectances and two spatial resolutions, i.e., 10 m, and 20 m. These were chosen to determine their effect on retrieved LAI accuracy and consistency. The results showed moderate R 2 , i.e.,~0.6 to~0.7 between SNAPderived LAI and in-situ LAI, but with high errors, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
1
28
1
1
Order By: Relevance
“…Negative values presented in the Sentinel-2 LAI can be considered outliers. Furthermore, some studies indicated that SNAP-derived LAI may significantly overestimate LAI values for different crops [ 65 , 66 ]; the comparison of the ZH-1 LAI map with the Sentinel-2 LAI map also confirmed this conclusion.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Negative values presented in the Sentinel-2 LAI can be considered outliers. Furthermore, some studies indicated that SNAP-derived LAI may significantly overestimate LAI values for different crops [ 65 , 66 ]; the comparison of the ZH-1 LAI map with the Sentinel-2 LAI map also confirmed this conclusion.…”
Section: Resultsmentioning
confidence: 55%
“…In addition, the ZH-1 hyperspectral satellite was the only commercial hyperspectral satellite that has been launched and networked in China. Kganyago et al compared the Sentinel-2 LAI product from the semi-arid agricultural landscape in Africa with global LAI products and showed that the R 2 values of Sentinel-2 LAI product and measured LAI could reach about 0.6–0.7, but the errors of RMSE and BIAS were relatively large, while the R 2 between theSentinel-2 LAI product and MODIS and Proba-V LAI products is about 0.55–0.8, and the RMSE error is small [ 65 ]. Hence, Sentinel-2 LAI product has some implications for characterizing LAI of agricultural crops.…”
Section: Discussionmentioning
confidence: 99%
“…Bothaville site, located at latitudes: 27°13ʹ0ʺS to 28°8ʹ0ʺS, and longitudes: 26°0ʹ0ʺE to 27° 05ʹ0ʺE, is characterized by warm and wet summers with average temperatures of ~18°C and an annual average rainfall of ~584 mm. Winters are cold, with average temperatures of about 5.1°C (Kganyago et al 2020a). On the other hand, the Harrismith site, located at latitudes: 28°0ʹ0ʺS to 29°0ʹ0ʺS and longitudes: 28°0ʹ0ʺE to 29°8ʹ0ʺE, is characterized by warm and wet summers with an average temperature of 19.2°C and an annual average rainfall of about 115 mm.…”
Section: Study Areamentioning
confidence: 99%
“…En este sentido el IAF predicho con información satelital, sobrestima el obtenido en campo. Dicho comportamiento también ha sido obtenido en otros estudios, por ejemplo, el llevado a cabo en cultivos como maíz y girasol, donde el IAF generado con el SNAP también sobrestima los valores de campo [42].…”
Section: Análisis Estadísticounclassified